Marketing Activities, Strategic Competition, and Firm Value. (22nd January 2018) - Ryoo, Juyoun; Lee, Cheolwoo; Jeon, Jin Q.; Choi, Hwanseok Winston
Abstract: This study extends the prior literature on the effect of marketing activities on firm value by investigating whether the nature of strategic competition affects financial outcomes differentially. Using the competitive strategy measure (CSM), we show that marketing spending is beneficial (detrimental) to firm value when the firm is in strategic substitutes (complements) and the efficacy is a decreasing function of the degree of industry competition. The relative competitive position of a firm in the industry—whether it is a leader or a follower—matters in the quality and size of the effect of marketing spending. By bifurcating the nature of strategic competition into strategic substitutes and complements, we disentangle the dichotomous effects of marketing activities on firm value. Copyright © 2018 ASAC. Published by John Wiley & Sons, Ltd.